Polarization-sensitive optical coherence tomography for ceramic materials inspection - Trojanowski, Michał; Kraszewski, Maciej; Strąkowski, Marcin Robert; Kosmowski, Bogdan; Pluciński, Jerzy (Photonics Letters of Poland, 2014)
Ceramics production is looking for a fast, reliable and non-destructive method that can be implemented on site for defect detection and analysis. In this paper we present polarization-sensitive optical coherence tomography (PS-OCT) as a method for defect inspection. Proposed extensions to standard OCT provide additional information for complete characterization of tested object. We compare OCT and microscope imaging that can easily detect enamel layer defects. The object under test is a sample ceramic plate with several defects occurring in production process. Results of OCT imaging show those defects are only in enamel layer without any effect on potsherd layer. Full Text: PDF References M. R. Strąkowski, J. Pluciński, B. B. Kosmowski, "Spectroscopic analysis for polarization sensitive optical coherent tomography", Phot. Lett. Poland 3, 128 (2011). CrossRef W. Drexler, J.G. Fujimoto, "Optical Coherence Tomography", Technology and Applications, Springer, 2008. CrossRef M. Bashkansky, M. D. Duncan and J. Reintjes, "Detection of near-surface microscopic defects in ceramics and other materials using optical coherence tomography", AIP Conf. 509. 1517 (2000). CrossRef J. P. Dunkers, F. R. Phelan, D. P. Sanders, M. J. Everett, W. H. Green, D. L. Hunston, R. S. Parnas, "The application of optical coherence tomography to problems in polymer matrix composites", Optics and Lasers in Engineering 35 (2001). CrossRef R. Su, E. Chang, P. Ekberg, L. Mattsson, S. Hyun Yun, "Perspectives of mid-infrared optical coherence tomography for inspection and micrometrology of industrial ceramics", 1st International Symposium on OCT4 NDT, Linz, 13-14 Febuary (2013). CrossRef M. Baskansky, M. D. Duncan, M. Kahn, D. Lewis III and J. Reintjes, "Subsurface defect detection in ceramics by high-speed high-resolution optical coherent tomography", Opt. Lett. 22, pp. 61-63 (1997). CrossRef K. Wiesauera, M. Pircherb and E. G. Otzingerb et al., "En-face scanning optical coherence tomography with ultra-high resolution for material investigation", Optics Express, 13 (3), pp. 1015-1025 (2005). CrossRef G. Song, K. Harding, "OCT for industrial applications", Proc. Of SPIE Vol. 85630N (2012). CrossRef B. Saleh, Introduction to subsurface imaging, Cambridge University Press, 2011. CrossRef R. Su, M. Kirillin, P. Ekberg, A. Roos, E. Sergeeva, L. Mattsson, "Optical coherence tomography for quality assessment of embedded microchannels in alumina ceramic", Opt. Express 20, 4603 (2012). CrossRef M. Bashkansky, M.D. Duncan, M. Kahn, D. Lewis Iii, J. Reintjes, "Subsurface defect detection in ceramics by high-speed high-resolution optical coherent tomography", Opt. Lett. 22, 61 (1997). CrossRef A.K.S. Braz, B.B.C. Kyotoku, R. Braz, A.S.L. Gomes, "Evaluation of crack propagation in dental composites by optical coherence tomography", Dent. Mater. 25, 74 (2009). CrossRef C. Sinescu, M.L. Negrutiu, C. Ionita, F. Topala, E. Petrescu, R. Rominu, D.M. Pop, L. Marsavina, R. Negru, A. Bradu, M. Rominu, A.G. Podoleanu, "Radiographic, microcomputer tomography, and optical coherence tomography investigations of ceramic interfaces", Proc. SPIE 7990, 79900W (2010). CrossRef A. F. Fercher, "Optical coherence tomography - principles and applications", Reports on Progress in Physics 66, 239 (2003). CrossRef D. Stifter, A. D. Sanchis Dufau, E. Breuer, K. Wiesauer, P. Burgholzer, O. Höglinger, E. Götzinger, M. Pircher, C. K. Hitzenberger, "Polarisation-sensitive optical coherence tomography for material characterisation and testing", Insight 47, 209 (2005). CrossRef M. R. Strąkowski, M. Kraszewski, M. Trojanowski, J. Pluciński, "Time-frequency analysis in optical coherence tomography for technical objects examination", Proc. SPIE 9132, 91320N (2014). CrossRef